background image

Proof.

Let

P 2

dom

S

,

Q 2

im

S

. Then there exist

P

0

and

Q

0

such that

(

P

;

Q

0

)

2

S

,

(

P

0

;

Q

)

2

S

.

P  Q

0

\ P

0

 Q

= (

P \ P

0

)

(

Q \ Q

0

)

(used the previous theorem).

T

F

fA  B j

(

A

;

B

)

2

S

g  P  Q

0

\ P

0

 Q

= (

P \ P

0

)

(

Q \ Q

0

)

 P  Q

. This implies that

\

F

fA  B j

(

A

;

B

)

2

S

g

=

\

F

fA  B j A 2

dom

S ;

B 2

im

S

g

=

\

F

f

A

B

j

A

2 h

up

i

dom

S ; B

2 h

up

i

im

S

g

:

On the other side

T

F

dom

S

T

F

im

S

=

T

F

f

A

B

j

A

2

up

T

F

dom

S ; B

2

up

T

F

im

S

g

??
If

A

2 h

up

i

dom

S

then

A

2

up

T

F

dom

S

. If

A

2

up

T

F

dom

S

then

8

S

2

P

F

: (

F \

S

F

S

=

/

; ) 9K 2

S

:

F \ K

=

/

;

)

8

S

2

P

F

: (

h

f

i

A

\

S

F

S

=

/

; ) 9K 2

S

:

h

f

i

A

\ K

=

/

;

)

8

S

2

P

F

: (

A

[

f

]

S

F

S

) 9K 2

S

:

A

[

f

]

K

)

8

S

2

P

F

:

h

f

i

S

F

S

=

S

F

hh

f

ii

S

;

8

S

2

PP

f

:

h

f

i

S

S

=

S

F

hh

f

ii

S

Proposition 52.

Equivalence of morphisms is an equivalence relation.

Proof.

Reexity.

Follows from the identity.

Symmetry.

Obvious.

Transitivity.

Let

f

g

and

g

h

. Then there exist a morphism

p

such that Src

p

v

Src

f

,

Src

p

v

Src

g

, Dst

p

v

Dst

f

, Dst

p

v

Dst

g

and

Src

f ;

Dst

f

p

=

f

and

Src

g;

Dst

g

p

=

g

and ??

??

f

=

Src

f ;

Dst

f

p

= (

Dst

p ,

!

Dst

f

)

p

(

Src

p ,

!

Src

f

)

y

g

=

Src

g;

Dst

g

p

= (

Dst

p ,

!

Dst

g

)

p

(

Src

p ,

!

Src

g

)

y

g

=

Src

g;

Dst

g

q

= (

Dst

q ,

!

Dst

g

)

q

(

Src

q ,

!

Src

g

)

y

h

=

Src

h;

Dst

h

q

= (

Dst

q ,

!

Dst

h

)

q

(

Src

q ,

!

Src

h

)

y

??
We have like:

(

X ,

!

A

)

p

= (

Y ,

!

A

)

q

and need

z

v

p; q

such that

(

Dst

z ,

!

A

)

z

= (

X ,

!

A

)

p

= (

Y ,

!

A

)

q:

Take

z

=

p

u

q

. Repeating this, we get:

g

=

Src

g;

Dst

g

p

= (

Dst

z ,

!

Dst

g

)

z

(

Src

z ,

!

Src

g

)

y

g

=

Src

g;

Dst

g

q

= (

Dst

z ,

!

Dst

g

)

z

(

Src

z ,

!

Src

g

)

y

??
Axiom:

X ,

!

A

is metamonovalued (requires order on the set of

all

objects).

Conjecture 53.

(

RLD

)

in

f

=

d

RLD

up

¡(

Src

f

;

Dst

f

)

f

for every funcoid

f

.

Proof.

Let

K

2

(

RLD

)

in

f

.

d

RLD

up

¡(

Src

f

;

Dst

f

)

f

=

d

RLD

up

¡(

Src

f

;

Dst

f

)

F

atoms

f

v

d

RLD

up

¡(

Src

f

;

Dst

f

)

F

FCD

f

X

A

Y

B

j A 2

F

(

Src

f

)

;

B 2

F

(

Dst

f

)

;

FCD

B v

f

g

=

d

RLD

up

¡(

Src

f

;

Dst

f

)

S

f

X

A

Y

B

j A 2

F

(

Src

f

)

;

B 2

F

(

Dst

f

)

;

FCD

B v

f

g

Pattern theorem 8.19.

Conjecture 54.

(

FCD

)

f

=

d

FCD

(¡(

A

;

B

)

\

GR

f

)

for every reloid

f

2

RLD

(

A

;

B

)

.

Proof.

x

FCD

y

2

atoms

(

FCD

)

f

,

x

RLD

y

/

f

,

??

Misc

15